Altered features of body composition in older adults with type 2 diabetes and prediabetes compared with matched controls. Issue 2 (16th February 2022) - Bell, Kirsten E.; Paris, Michael T.; Avrutin, Egor; Mourtzakis, Marina
Abstract: Background: Ageing is accompanied by muscle loss and fat gain, which may elevate the risk of type 2 diabetes (T2D). However, there is a paucity of data on the distribution of regional lean and fat tissue in older adults with T2D or prediabetes compared with healthy controls. The objective of this study was to compare regional body composition [by dual‐energy x‐ray absorptiometry (DXA)], muscle and subcutaneous adipose tissue (SAT) thicknesses (by ultrasound), and ultrasound‐based muscle texture features in older adults with T2D or prediabetes compared with normoglycaemic controls. Methods: Eighteen adults > 60 years with T2D or prediabetes (T2D group) were individually matched to normoglycaemic participants [healthy matched (HM) group] for age (±5 years), sex, and body fat (±2.5%). In a single study visit, all participants received a whole‐body DXA scan and ultrasound assessment of the abdomen and anterior thigh. At these two landmarks, we used ultrasound to measure muscle and SAT thickness, as well as texture features of the rectus femoris and rectus abdominis. We also conducted an exploratory subanalysis on a subset of participants ( n  = 14/18 in the T2D group and n  = 10/18 in the HM group) who underwent additional assessments including strength testing of the knee extensors (using a Biodex dynamometer), and a fasting blood sample for the measurement of circulating markers of glucose metabolism [glucose, insulin, c‐peptide, and the homoeostatic model assessment of insulin resistance (HOMA‐IR)]. Results: The T2D group was 72 ± 8 years old (mean ± SD), predominantly male ( n  = 15/ 18; 83%), and overweight (BMI: 27.8 ± 4.2 kg/m 2, 33.2 ± 5.3% body fat). DXA‐derived upper arm lean mass was 0.4 kg greater ( P  = 0.034), and leg fat mass was 1.4 kg lower ( P  = 0.048), in the T2D vs. HM group. Ultrasound‐based texture features were distinct between the groups [rectus abdominis blob size: 0.07 ± 0.06 vs. 0.30 ± 0.43 cm 2, P  = 0.045; rectus femoris local binary pattern (LBP) entropy: 4.65 ± 0.05 vs. 4.59 ± 0.08 A.U., P  = 0.007]. When all participants who underwent additional assessments were pooled ( n  = 24), we observed that certain ultrasound‐based muscle texture features correlated significantly with muscle strength (rectus abdominis histogram skew vs. power during an isokinetic contraction at 60°/s: r  = 0.601, P  = 0.003) and insulin resistance (rectus femoris LBP entropy vs. HOMA‐IR: r  = 0.419, P  = 0.042). Conclusions: Our findings suggest a novel body composition phenotype specific to older adults with T2D or prediabetes. We are also the first to report that ultrasound‐based texture features correspond with functional outcomes. Future larger scale studies are needed to uncover the mechanisms underpinning these regional body composition differences.